Can food-for-work programmes reduce vulnerability? - Christopher B. Barrett; Stein Holden; Daniel C. Clay (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Food-for-work (FFW) programmes have been widely heralded as a means of providing self-targeting transfers coupled with investment in public goods. This paper reviews the changing context that has sparked such interest in FFW, the simple theory that makes it so conceptually appealing, and conceptual problems with that simple theory, all illustrated with empirical examples, primarily from east Africa. We conclude with an attempt at distilling some useful rules of thumb as to when, how and why FFW can serve effectively as short-term insurance, a longer-term rehabilitation and development intervention, or both. – famine ; food aid ; poverty ; public employment programmes ; transfers
Keywords: O12; Q18; O15; O20; I3; 330; Aktivierende Sozialhilfe; Nahrungsmittelsubvention; Ostafrika